2014
DOI: 10.1080/03004430.2014.884086
|View full text |Cite
|
Sign up to set email alerts
|

Preschool teachers' skills in teaching music: two steps forward one step back

Abstract: This study investigates through observations and interviews what importance further education has for preschool teachers' practice in two music-profiled preschool and their way of conceptualising it. A distinction between music as a method for teaching, on the one hand, and as a content of knowledge, on the other, is used in the analysis. The result shows that the teachers act confidently in dealing with music; both in spontaneous and planned activities, and that they show competence in teaching music to the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 20 publications
(22 reference statements)
3
24
0
2
Order By: Relevance
“…and!Wallerstedt! [10]!points!to!alternative!ways!of!using!music!in!preschool,!either!as!a!method! for!developing!e.g.!language!or!intercultural!understandings!or!as!content!for!learning!in!itself.!…”
Section: Introduction)mentioning
confidence: 99%
“…and!Wallerstedt! [10]!points!to!alternative!ways!of!using!music!in!preschool,!either!as!a!method! for!developing!e.g.!language!or!intercultural!understandings!or!as!content!for!learning!in!itself.!…”
Section: Introduction)mentioning
confidence: 99%
“…Participants who visited visual art exhibitions several times per year also conducted: music activities more often than participants who visited exhibitions once per year, t = 2.62, p = .013, or never, t = .72, p = .010; music-creative activities more often than participants who visited exhibits once per year, t = 2.99, p = .004, or never, t = 3.31, p = .001; art activities more often than participants who visited exhibitions once per year, t = 2.35, p = .028, or never, t = 2.14, p = .049; visual-creative activities more often than participants who visited exhibitions once per year, t = 2.82, p = .007, or never, t = 3.89, p = .0001. Whereas some authors (Ehrlin & Wallerstedt, 2014) found that preschool teachers consider music and visual art skills as innate, Kempe and West (2010) consider those skills to be conditioned. After reviewing 30 years of education research focused on further art training designed for pre-service teachers, Garvis and Riek (2010) reported three fundamental problems: insufficient time devoted to art education, lack of confidence required to participate in art activities, and the effects of previous experiences in the arts on the willingness to conduct and participate in art activities.…”
Section: Resultsmentioning
confidence: 99%
“…The aforementioned authors emphasise the necessity for further research on the topic of self-efficacy in art education because of its importance for development in early childhood. Ehrlin and Wallerstedt (2014) concluded that the majority of teachers in early childhood and preschool settings believe that some children are born with innate talent for music skills and artistic knowledge. However, West and Kempe (2010) argue that these types of beliefs are the products of social conditioning and that musical knowledge and skills are a set of competencies that can be developed as any other competency, given the appropriate environmental conditions (Ehrlin & Wallerstedt, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Ehrlin and Wallerstedt (2014) concluded that the majority of teachers in early childhood and preschool settings believe that some children are born with innate talent for music skills and artistic knowledge. However, West and Kempe (2010) argue that these types of beliefs are the products of social conditioning and that musical knowledge and skills are a set of competencies that can be developed as any other competency, given the appropriate environmental conditions (Ehrlin & Wallerstedt, 2014). Garvis and Riek (2010) reported that 30 years of pedagogical research in the area of professional development among pre-service early childhood teachers in music and the arts highlights the following three problems: (a) the lack of time allocated for their art education, (b) the educators are insecure when participating in art activities and (c) previous experiences affect their current participation in art activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation